Efek Kepemimpinan Transformasional, Power Distance Dan Followership Terhadap Kemampuan Pengambilan Keputusan Karyawan - Muchamad Lukman Fauzi; Survival Survival; Mulyono Mulyono (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The purpose of this study was to determine “the effect of transformasional leadership, power distance and followership on decision making abilities” (Study on employees of PT. Telkom Akses Malang). The population in this study were all employees of PT. Telkom Akses Malang, totaling 233 people. The sampling technique in this study used “Non Probability Sampling”, and the sampling method in this study was “Proportional Cluster Sampling”, with a total of 67 respondents. Data were analyzed by Multiple Linear Regression. Based on raw data or primary data collected from respondents, it is then processed through SPSS for windows statistical data processing.The results of the study prove that transformasional leadership, power distance and followership simultaneously and partially have a positif and significant effect on the decision making abilities of employees of PT. Telkom Akses Malang, where transformasional leadership has a dominant influence on the decision making ability of employees of PT. Telkom Akses Malang.